Modeling of fluidized-bed reactor for the production of syngas by using carbon dioxide and methane - Wong, Kar Chun, 1988-, author; Nor Aishah Saidina Amin, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper Sarjana Muda Kejuruteraan (Kimia) - Universiti Teknologi Malaysia, 2012